The Rhetoric of Green Hotels - Frandsen, Finn; Johansen, Winni (HERMES - Journal of Language and Communication in Business, 2001)
The last two decades have seen environmentalism become a core value in western societies. This evolution, and in particular the rise of environmental consumerism, has not only forced the marketplace to be more responsive to products and services promising environmental responsibility, but has also created new types of communication, including new text genres and a new rhetoric. The purpose of this article is to analyse the environmental rhetoric of green hotels in Denmark. The article briefly presents the differences and similarities between political and commercial green discourse and then discusses the paradoxes of green marketing as reflected in the texts of some of the most important green hotel chains and associations of green hotels in Denmark. The article devotes its analysis to select rhetorical aspects of two genres, the green hotel brochure and the green card or "towel card".